Recurrence of acute otitis media at preschool age in Sweden. Issue 1 (February 1994) - Rasmussen, F
Abstract : STUDY OBJECTIVE–The probability of recurrence of acute otitis media during the preschool years was investigated. SETTING–All children born in a semirural Swedish municipality were followed up from birth to their 7th birthday. DESIGN–Information about visits to physicians for acute otitis media was collected retrospectively at all primary health care centres and at paediatric and ear, nose, and throat departments. Check up visits after acute otitis media were excluded. Life table methods were used for analyses. PARTICIPANTS–All 1306 children born in the study municipality between 1977 and 1981 were included. Children who moved from the study area during the follow up years (24%) were included in the analyses from the date of birth to the date they left the area. MAIN RESULTS–At age 3 years, 38%, 10%, and 4% of the children had made at least one, three, and five visits respectively to a physician because of acute otitis media. By their 7th birthday, 61%, 24%, 12%, and 2% of the children had made at least one, three, five, and 10 visits respectively to a physician because of this disorder. CONCLUSIONS–A strong association was found between the number of visits made for acute otitis media during the first year of life and the probability of visiting a physician because of this disorder over the next 12 months.